INNOVATIVE DEVELOPMENT AND COMPETITIVENESS OF THE INDUSTRIAL SECTOR INBULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article presents methods for assessing the innovative development and compe-titiveness of the industrial sector in the Republic of Bulgaria. Guidelines and recommendations for their acceleration are indicated. A cross-section of the Bulga-rian industry is also made, assessing the innovative acceleration of the technologies used.